Under the egg - Fitzgerald, Laura Marx; Dial Books for Young Readers (New York, New York : Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2014)
Her grandfather's dying words lead thirteen-year-old Theodora Tenpenny to a valuable, hidden painting she fears may be stolen, but it is her search for answers in her Greenwich Village neighborhood that brings a real treasure.
Middle School.
790 Lexile.
Accelerated Reader
Reading Counts!
Keywords: Neighborhoods -- Juvenile fiction; Art -- Juvenile fiction; Friendship -- Juvenile fiction; Recluses -- Juvenile fiction; Holocaust, Jewish (1939-1945) -- Juvenile fiction; Greenwich Village (New York, N.Y.) -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Detective and mystery stories; Neighborhoods -- Fiction; Art -- Fiction; Friendship -- Fiction; Recluses -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Greenwich Village (New York N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Mystery and detective stories; Detective and mystery fiction